The Level of Conceptual Understanding of Symmetry in Mathematics among Students of Tafila Technical University - Bani Ata, Rasha Abd-Alrahman; ALRawajfa, Ayman Eid (Journal of Educational and Psychological Sciences, 2021)
The study aimed to reveal the level of conceptual understanding of symmetry in mathematics among students of Tafila Technical University, and to know the existence of statistically significant differences in the level of their conceptual understanding of symmetry due to variables of gender, university specialization and level of the cumulative rate. The sample consisted of (135) students from the course of calculus (2). In order to achieve the study's objectives, a test for the conceptual understanding of symmetry was manufactured, verify its validity and reliability, and test the study sample for it. The results showed that the students' conceptual understanding of symmetry in general, their understanding of reflexive symmetry and glide reflexive symmetry was mediation, the level of students' understanding of rotational symmetry and symmetry as a network of symmetries was decrease, while the level of their understanding of translational symmetry was high. The results showed that there were no statistically significant differences in the level of the students' conceptual understanding of symmetry attributed to the variables of gender, university specialization and their level of the cumulative rate. The study concluded that more studies will be conducted that investigate the conceptual understanding of several mathematical concepts, including other samples, problems, universities and courses.
Keywords: Conceptual Understanding; Symmetry in Mathematics; Tafila Technical University